2016
DOI: 10.3390/economies4040028
|View full text |Cite
|
Sign up to set email alerts
|

Remittances, Development Level, and Long-Run Economic Growth

Abstract: This paper seeks to enrich the field of research on the topic of the impact of remittances on long-run economic growth. Using an unbalanced panel data covering a sample of 116 countries with different development levels over the period 1990-2014, we studied the interaction between remittances and the level of economic development, as well as its impact on long-run economic growth-because the impact of remittances could be influenced by the development level of the receiving countries. In parallel, we explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 63 publications
1
21
0
1
Order By: Relevance
“…It can therefore be concluded that the initially lower level of development is conducive to higher dynamics of GDP growth. The variables found in the second and third positions of the ranking, that is, X 2 , gross national savings, and X 12 , gross fixed capital formation, respectively, refer to a similar subject, which can have a considerable impact on the dynamics of economic growth, both theoretically and in practice (Matuzeviciute and Butkus [69], Danileviciene and Lace [70]). Gross fixed capital formation directly demonstrates the proportion of GDP that is further invested, and the gross national savings, understood in the Keynesian approach, can be also ultimately treated as an investment, which is axiomatic in closed economies.…”
Section: Resultsmentioning
confidence: 99%
“…It can therefore be concluded that the initially lower level of development is conducive to higher dynamics of GDP growth. The variables found in the second and third positions of the ranking, that is, X 2 , gross national savings, and X 12 , gross fixed capital formation, respectively, refer to a similar subject, which can have a considerable impact on the dynamics of economic growth, both theoretically and in practice (Matuzeviciute and Butkus [69], Danileviciene and Lace [70]). Gross fixed capital formation directly demonstrates the proportion of GDP that is further invested, and the gross national savings, understood in the Keynesian approach, can be also ultimately treated as an investment, which is axiomatic in closed economies.…”
Section: Resultsmentioning
confidence: 99%
“…Cass [52] and Koopmans [53] improved the neoclassical growth model by introducing the optimization analysis of the final consumer, which permitted the determination of the saving rate. The developing countries tend to recover the gap from developed countries through positive economic growth rates, influenced by human capital [54][55][56][57].…”
Section: Methodsmentioning
confidence: 99%
“…The results for the seven countries are similar with the one obtained by Golitsis et al (2018) for Albania, regarding the Granger-causality between Remittances and GDP. Giuliano and Ruiz-Arranz (2009) studying 100 countries, obtained a positive influence of remittances on the economic growth; Siddique, Selvanathan, and Selvanathan (2012), Matuzeviciute and Butkus (2016) and Meyer and Shera (2016) also concluded that the volume of remittances stimulates economic growth for some receiving countries.…”
Section: Robustness Analysismentioning
confidence: 96%